2015
DOI: 10.5543/tkda.2015.72025
|View full text |Cite
|
Sign up to set email alerts
|

Brucellosis impairs endothelial functions in chronic symptomatic patients without overt cardiac involvement

Abstract: Brucellosis impairs endothelial functions in chronic symptomatic patients without overt cardiac involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In other case studies, it has been reported that mycotic pseudoaneurysm usually is due to trauma to the arterial wall with subsequent contamination [6, 1621]. The arterial segment might be disrupted when an invasive infection is able to directly lodge in the artery or the vasa vasorum, especially with an intimal defect in the arterial wall such as an arteriosclerotic plaque [6, 19, 20]. In our case, the arteriosclerotic plaques were on CTA imaging.…”
Section: Discussionmentioning
confidence: 65%
“…In other case studies, it has been reported that mycotic pseudoaneurysm usually is due to trauma to the arterial wall with subsequent contamination [6, 1621]. The arterial segment might be disrupted when an invasive infection is able to directly lodge in the artery or the vasa vasorum, especially with an intimal defect in the arterial wall such as an arteriosclerotic plaque [6, 19, 20]. In our case, the arteriosclerotic plaques were on CTA imaging.…”
Section: Discussionmentioning
confidence: 65%
“…It has been shown that infections constitute a risk factor for atherosclerosis and contribute to the chronic inflammatory process through direct or indirect effects [ 13 , 14 , 26 30 ]. In addition, in the study of Gursoy et al [ 35 ], it was shown that endothelial functions are impaired in patients with Brucellosis.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, it has been suggested that the indirect effect of cytokines or toxins may cause an immune reaction to brucella antigen on the vascular walls, as well as direct endothelial damage and damage to the vascular endothelium [ 18 , 19 ]. Gürsoy et al [ 20 ] stated that it can disrupt endothelial functions in patients with brucella infection without causing chronic symptoms. It has been reported that some microorganisms such as Chlamydia pneumoniae and Human cytomegalovirus can cause endothelial dysfunction by affecting the artery walls [ 21 ].…”
Section: Discussionmentioning
confidence: 99%